Attenuated virulence of chitin-deficient mutants of Candida albicans. - Bulawa, C E (1995)
We have analyzed the role of chitin, a cell-wall polysaccharide, in the virulence of Candida albicans. Mutants with a 5-fold reduction in chitin were obtained in two ways: (i) by selecting mutants resistant to Calcofluor, a fluorescent dye that binds to chitin and inhibits growth, and (ii) by disrupting CHS3, the C. albicans homolog of CSD2/CAL1/DIT101/KT12, a Saccharomyces cerevisiae gene required for synthesis of approximately 90% of the cell-wall chitin. Chitin-deficient mutants have no obvious alterations in growth rate, sugar assimilation, chlamydospore formation, or germ-tube formation in various media. When growing vegetatively in liquid media, the mutants tend to clump and display minor changes in morphology. Staining of cells with the fluorescent dye Calcofluor indicates that CHS3 is required for synthesis of the chitin rings found on the surface of yeast cells but not formation of septa in either yeast cells or germ tubes. Despite their relatively normal growth, the mutants are significantly less virulent than the parental strain in both immunocompetent and immunosuppressed mice; at 13 days after infection, survival was 95% in immunocompetent mice that received chs3/chs3 cells and 10% in immunocompetent mice that received an equal dose of chs3/CHS3 cells. Chitin-deficient strains can colonize the organs of infected mice, suggesting that the reduced virulence of the mutants is not due to accelerated clearing.